Solutions for heat or cold discharge from encapsulated phase-change materials - Vitorino, Nuno
Stable, convergent, and fast computing codes have been developed to describe heat or cold discharge from encapsulated phase-change materials (PCMs). Numerical algorithms are based on previous transformations of relevant variables to yield immobilization of the moving boundary and also a flat-like condition to enhance convergence of the computing codes. These algorithms are used to analyze heat transfer limitations imposed by the low conductivity of the solidifying PCM layer and the mixed control related to the thermal resistance of the encapsulated wall and/or heat transfer limitations to the external fluid. The stability and the convergence of the codes are analyzed by varying the mesh size, and the relative time step, and are also compared with a space grid method solution. Quasi-steady-state solutions are also proposed and their applicability examined.